2020
DOI: 10.3390/su12104263
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Sustainable Indoor Lighting Design: Effects of Artificial Light on the Emotional State of Adolescents in the Classroom

Abstract: In recent years, articles have been published on the non-visual effects of light, specifically the light emitted by the new luminaires with light emitting diodes (LEDs) and by the screens of televisions, computer equipment, and mobile phones. Professionals from the world of optometry have raised the possibility that the blue part of the visible light from sources that emit artificial light could have pernicious effects on the retina. The aim of this work is to analyze the articles published on this subject, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 88 publications
0
12
0
1
Order By: Relevance
“…The calibration is traceable to the National Standard for Luminous Intensity and Luminous Flux. This spectroradiometer was previously used in other studies regarding emissions from LED lamps [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration is traceable to the National Standard for Luminous Intensity and Luminous Flux. This spectroradiometer was previously used in other studies regarding emissions from LED lamps [11].…”
Section: Methodsmentioning
confidence: 99%
“…Since blue light acts as a neurophysiological stimulant, several therapeutic effects have been described, from depression [9] to a reduction of blood pressure [10]. Besides the positive influence, some studies have indicated negative effects on the balance of circadian cycles and on the quality of sleep after long exposures to blue light, mainly from mobile phones [11]. On the other hand, some studies have also reported negative effects on the eye retina, most of which are based on the analysis of cells that were irradiated with blue light.…”
Section: Introductionmentioning
confidence: 99%
“…It includes aspects such as air quality, comfortable temperature, air quality and adequate humidity levels. Research has shown that IEQ has a relevant impact in the performance of those who occupy the space [17][18][19]. IEQ is a value that indicates to what extent the energy used for the construction and use of a building is useful or efficient.…”
Section: Resourcesmentioning
confidence: 99%
“…It includes previously mentioned aspects such as air quality, comfortable temperature, noise pollution, all of those aspects related to this study. Research has shown that IEQ has a relevant impact on the performance of those who occupy the space [28][29][30]. Besides the before-mentioned health, economic and environmental impacts, poor IEQ in buildings makes its occupants less happy and less productive, specifically in workplaces [31].…”
Section: Introductionmentioning
confidence: 99%